Evaluation of complications of root canal treatment performed by undergraduate dental students. Issue 1 (1st January 2017) - AlRahabi, Mothanna K.
ABSTRACT: This study evaluated the technical quality of root canal treatment (RCT) and detected iatrogenic errors in an undergraduate dental clinic at the College of Dentistry, Taibah University, Saudi Arabia. Dental records of 280 patients who received RCT between 2013 and 2016 undertaken by dental students were investigated by retrospective chart review. Root canal obturation was evaluated on the basis of the length of obturation being ≤2 mm from the radiographic apex, with uniform radiodensity and good adaptation to root canal walls. Inadequate root canal obturation included cases containing procedural errors such as furcal perforation, ledge, canal transportation, strip perforation, root perforation, instrument separation, voids in the obturation, or underfilling or overfilling of the obturation. In 193 (68.9%) teeth, RCT was adequate and without procedural errors. However, in 87 (31.1%) teeth, RCT was inadequate and contained procedural errors. The frequency of procedural errors in the entire sample was 31.1% as follows: underfilling, 49.9%; overfilling, 24.1%; voids, 12.6%; broken instruments, 9.2%; apical perforation, 2.3%; and root canal transportation, 2.3%. There were no significant differences ( p > 0.05) in the type or frequency of procedural errors between the fourth- and fifth-year students. Lower molars (43.1%) and upper incisors (19.2%) exhibited the highest and lowest frequencies of procedural errors, respectively. The technical quality of RCT performed by undergraduate dental students was classified as 'adequate' in 68.9% of the cases. There is a need for improvement in the training of students at the preclinical and clinical levels.